Metamorfoses de um rei: imagens de vilania em "Richard III" de William Shakespeare - Gloria Maria Guine de Mello (2013)
Metamorfoses de um Rei: Imagens de Vilania em Richard III, de William Shakespeare aims at discussing the villains characterization in the following films: Richard III, 1955, directed by Laurence Olivier, England; Richard III, 1995, directed by Richard Loncraine, USA, and Looking for Richard, 1996, directed by Al Pacino, USA considered as a creative chain triggered by William Shakespeares play Richard III. It also includes Salvador Dalís oil on canvas Portrait of Laurence Olivier in the role of Richard III, 1955. The works are analyzed with the support of theories on villainy, adaptation and intermediality, reaching conclusions that point to the fact that different approaches to the adaptation of Shakespeares play into the movies are influenced by circumstances posed by the contextual qualifying aspects and the operational qualifying aspect as defined by Lars Elleström. A short final chapter has been added considering the recent finding of Richard IIIs death remains in Leicester, England, and its possible consequences on future studies of the historical as well as the theatrical character.